Predictors of outcome in patients with tuberculous meningitis - Hosoglu, S; Geyik, MF; Balik, I; Aygen, B; Erol, S; Aygencel, TG; Loeb, M (Int Union Against Tuberculosis Lung Disease (I U A T L D), 2002)
OBJECTIVE: To assess predictors of mortality and neurological sequelae in patients with tuberculous meningitis (TBM). METHODS: Patients with TBM treated at 12 university hospitals in Turkey between 1985 and 1997 were evaluated using a standardised protocol applied retrospectively. Variables associated with hospital mortality as well as with the presence of neurological sequelae at 6 months were determined using logistic regression models. RESULTS: Four hundred and thirty-four patients between the ages of 13 and 83 years (mean 33 years) were evaluated. Sixty-eight per cent of these patients presented with Medical Research Council Stage H or III. One hundred and one patients (23.3%) died and 67 (27%) of evaluable survivors had neurological sequelae. In multivariable analysis, convulsion (OR 3.3, 95%CI 1.2-9.0, P = 0.02), comatose mental status (OR 6.0, 95%CI 3.6-10.2, P = 0.01), and delayed or interrupted treatment (OR 5.1, 95%CI 2.4-11.2, P = 0.01) were shown to be predictors for mortality. The presence of extra-meningeal tuberculosis (OR 2.1, 95%CI 1.1-4.2, P = 0.035), cranial nerve palsy (OR 2.6, 95%CI 1.4-4.2, P = 0.01), hemiparesia/focal weakness (OR 9.3, 95%CI 3.8-22.6, P = 0.01), hemiplegia/multiple neurological deficit (OR 7.1, 95%CI 2.14-23.38, P = 0.01) and drowsiness (OR 4.2, 95%CI 2.04-8.82, P = 0.01) were independent predictors of neurological sequelae at 6 months following hospital discharge. CONCLUSION: The results of this study emphasise the importance of prompt and uninterrupted anti-tuberculosis therapy for tuberculous meningitis. The presence of seizures or coma on admission to hospital are important predictors for mortality, while the presence of focal neurological signs is a predictor for persistent neurological sequelae in survivors.
Keywords: tuberculous meningitis; outcome; independent factors